Adult Learner Success Stories: The Impact of Shifting Political Discourses on Adult Literacy Education - M. Carolyn Clark; Jennifer A. Sandlin (Adult Education Research Conference, 2007)
This study examines the impact of shifting political discourse on adult literacy success stories. Those shaped by a liberal democratic discourse portray programs as the means students use to achieve their educational goals, while those framed within a neoconservative discourse attribute the students’ success to their own efforts through a type of bootstrapism.